Linguistic-semiotic analysis of humorous vignettes about covid-19 - Loayza-Maturrano, Edward Faustino (2021)
This article proposes an analysis matrix to identify the meanings and cognitive strategies used when developing humorous vignettes. The objective of the study is to linguistically and semiotically analyze the humorous cartoons of the main newspapers of the Metropolitan Lima press in times of pandemic. The research methodology is qualitative of the discourse analysis type. The results show the use of the type of black humor, the frequent use of implicatures and presuppositions within the pragmatic phenomena of discourse. The results also allowed us to observe that the linguistic innovations of the balloons and the graphic resources in the vignettes reflect the executive process in the thinking-meaning of the images with humorous intention. The main conclusion is that the linguistic-semiotic analysis of the iconoglossic discourse of the humorous cartoons made it possible to explain the sociopolitical situation of society due to Covid-19 and the ideology of the newspapers, as well as to determine the evidence of cognitive processes of language such as metaphor conceptual, conceptual metonymy and conceptual hyperbole. The use of the analysis matrix is ​​recommended in the interpretation of discontinuous texts.